Nilai Tukar, Inflasi dan Return Saham dengan Jenis Industri sebagai Variabel Pemoderasi - Nugraha, Gede Made Ananda Cipta; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
Stock returns are the results obtained by investors from investment activities and rewards for their courage in taking the risk of investing in stocks in the capital market. The research objective is to determine the effect of exchange rates and inflation on stock returns with the type of industry as a moderating variable. The research was conducted in all companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The number of samples taken was 226 companies using proportionate stratified random sampling technique. The analysis technique used is moderation regression analysis. The results showed that the exchange rate and inflation had a negative effect on stock returns. The impact of the weakening exchange rate and rising inflation on stock returns is stronger in the financial industry. Keywords: Exchange Rate; Inflation; Stock Return; Industry Type